Crystal structure of 4-(dimethylamino)pyridinium dibromido-tris(4-chlorophenyl-κC)stannate(IV), C25H23Br2Cl3N2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C25H23Br2Cl3N2Sn, monoclinic, P21/c (no. 14), a = 10.9372(1) Å, b = 23.1045(1) Å, c = 11.1856(1) Å, β = 106.942(1)°, V = 2703.91(4) Å3, Z = 4, Rgt(F) = 0.0167, wRref(F2) = 0.0393, T = 100 K.